The differential influence of women's residential district on their risk of entering motherhood and first marriage : a discrete time multilevel analysis of Western German panel data, 1984 - 1999 - Karsten Hank (Deutsches Institut für Wirtschaftsforschung (DIW), 2002)
To begin with, we sketch a general multilevel model of regional social contexts and individual family formation behavior, where particular attention is paid to the determinants of the actor's situation. Then a set of bridge hypotheses is proposed, on which the empirical investigation of the relationship between properties of the spatial context and women's entry into motherhood and first marriage is based. Individual-level data from the German Socio-Economic Panel Study (GSOEP) are merged with a rich set of district-level contextual data to estimate first birth and marriage probabilities of western German women during the 1980s and 1990s. None of the estimated multilevel discrete-time logit models provides conclusive evidence for an autonomous contextual influence on women's entry into parenthood. We find, however, a persistent regional effect on the risk of entering first marriage, which we attribute to local nuptiality customs. Variations therein, e.g. regarding the timing of marriage, must probably be understood as the principal origin of different patterns of fertility across western German districts.
Keywords: 330; Ehe; Fruchtbarkeit; Familienökonomik; Region; Soziale Beziehungen; Regionale Disparität; Schätzung; Alte Bundesländer; Deutschland